BAHASA DAN ETNISITAS: STUDI TENTANG NAMA-NAMA RUMAH MAKAN PADANG - Wijana, I Dewa Putu Wijana Putu (Masyarakat Linguistik Indonesia, 2016)
This article is concerned with the naming practices of Padang restaurants in several cities in Indonesia. The results of the present study show that there are two strategies used by the Padang restaurant’s owners for the naming practices, namely divergence strategy and convergence strategy. The first strategy is carried out by using Minangkabau words, while the second one by using Indonesian words or foreign loan words which are already integrated into Indonesian vocabulary. Semantically the words used as the basis of naming refer to various concepts reflecting values and world views of Minangkabau people.